Etuden fur Timpani: Heft 3 - HOCHRAINER, Richard (Ludwig Doblinger (Bernhard Hermansky), 1983)
In the part of this methode, "Etuden fur Timpani", the study of which is a pre-requisitite for continuing here, the bars of rhythms are as important for timpanists and percussionists as scales and broken chords are for any other instrumentalist.